Determinant of Financial Company Profitablity - Suwinto Johan (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The purpose of the paper is to study the determinants of finance companies profitability. The finance company industry is one of main contributors of Indonesia economic growth during the last 15 years. Total asset of the industry is more than IDR 500 Trillion in 2018. The industry also considered as one the fastest growing industries during the last 15 year. We have analyzed the five main financial ratios and alliance impact as determinants of finance companies’ profitability. The profitability is measured by profit size, return on asset and return on equity. The financial ratios are firm size, efficiency ratio, leverage ratio, asset allocation ratio, and profitability ratio. We use data panel. The empirical results show that the determinants of finance companies’ profitability are leverage ratio, firm size, and efficiency ratio. However, the determinants of return on asset are net profit margin and efficiency ratio. On the contrary, the determinants of return on equity are firm size and equity size. Firm size has negative influence on return on equity. All determinants are significant at less than 1%, only efficiency ratio on profitability has significant at less than 10%. Keywords: financial ratio, financial institution, profitability, return on assets, return on equity